Use of body and beard donor hair in surgical treatment of androgenic alopecia - Arvind Poswal (Indian Journal of Plastic Surgery)
Objectives: Follicular unit transplant is a widely used surgical treatment for androgenic alopecia. However, for patients with extensive hair loss (Norwood 5 and above), scalp donor hair are not sufficient to cover all areas of baldness. This study aims to assess suitability of beard and body donor hair when transplanted to the scalp. Materials and Methods: In 35 male patients having varying degrees of androgenic alopecia, body and beard donor hair were extracted by follicular unit extraction method (under local anesthesia). They were transplanted in different locations of the scalp. Follow-up was carried out at various intervals (6 months to 2 years). The hairs were observed for colour, curl and calibre. Results: In all the patients, there was no change in the colour, curl or calibre of the transplanted body/beard hair. They maintained the same characteristics as in their original location. Conclusion: Body and beard hair can be used as additional donor resource for treating androgenic alopecia. These hairs, however, do not change their colour, curl, and shaft diameter (calibre). Thus, proper planning is a must when using the different types of donor hair for transplanting.